Awareness Regarding Cervical Cancer among Women Residing in Bharatpur, Chitwan - Shrestha, Laxmi; Ranabhat, Mina Kumari; Thapa, Basanta; Paudel, Radha (Nepalese Journal of Cancer, 2020)
Introduction: Cervical cancer is one of the most prevalent cancer affecting women globally. It is the fourth most common cancer in women and the seventh overall. Cervical cancer can be cured and prevented by regular pelviccheck-up, screening test and vaccination against human papilloma virus. The objective of this study was to find out awareness regarding cervical cancer among women aged 18-49 years residing in Bharatpur MetropolitanCity-5, Chitwan. Methods: A community based descriptive cross-sectional research design was used, 186 women were selected using simple random sampling method. Structured interview schedule was used to collect the data within 2weeks. The collected data was entered in Epi data 3.1 and exported into IBM SPSS version 20. Data was analysed in terms of descriptive and inferential statistics. Results: The study revealed that 72.6% of the women were >30 years and 93% of women were literate, among them 35.2% had completed secondary level of education. It was found that only 28.0% of women had good level of awareness and 43.5% of them had poor level of awareness regarding cervical cancer. There was statistically significant relationship between level of awareness with age (p=0.029), ethnicity (p=0.013), marital status (p=0.018) and heard about organism that causes cervical cancer (p=<0.001). Conclusions: Based on the findings of the study, it is concluded that, almost half of the women have poor level of awareness regarding cervical cancer. Hence, there is need for community awareness program on cervical cancer, its screening and preventive measures through the medium of health personnel, friends and mass media.